PENDUGAAN STATUS PECEMARAN AIR DENGAN PLANKTON SEBAGAI BIOINDIKATOR DI PANTAI KABUPATAN BANYUWANGI JAWA TIMUR. - Andi Kurniawan (Jurnal Kelautan, 2011)
Coastal areas of Banyuwangi Residence are location that exposed to industrial and settlement activity. This condition makes much waste contaminated coastal area of Banyuwangi Residence, and can decrease quality of the area. Plankton is organism that live depended on quality of aquatic environment. Several species of plankton can live on contaminated water. So we can use diversity of plankton as water pollution indicator. The aim of this research is to know coastal contamination status in Banyuwangi Residence. Plankton was used as bioindicator to anticipating coastal pollution. This research is conducted at the dry season on 2010. The result of this research showing the value of shannon diversity index are : 0.60796, 1.17653, 2.25307, 0.54356. This value showing water pollution happened in coastal area of Banyuwangi Residence. The level of water pollution that happened is middle level until heavy level.  Keywords  : Banyuwangi, plankton, bio-indicator, pollution. Diversity indeks